Determinación de la composición química, propiedades físicas y evaluación de la actividad biológica del aceite esencial de individuos con flores masculinas de la especie Hedyosmum racemosum (Ruiz & Pav.) G.Don de la provincia de Loja - Chamba Granda, Dalila Fernanda (2015)
Hedyosmum racemosum is a dioecious plant, which growing wild on medium-high elevations. Essential oil was extracted from the aerial parts by hydrodistillation. The chemical composition of the essential oil was determined by gas chromatography-mass spectrometry (GC/MS) and the flame ionization detector (GC/FID). The biological activity was evaluated by the broth microdilution method and was expressed as minimum inhibitory concentrations (MICs). Antioxidant activity was determined by method of free radical DPPH and ABTS+. Physical properties of essential oil were also determined. Forty-five compounds were identified, representing 98,87% of the oil. Main compounds were α-pinene (7.48%), α-phellandrene (28.24%), limonene (3.68%), (Z) -β-ocimene (2.88%), linalool (4,19%), estragole (21.82%), Methyl Eugenol (5.38%), Germacrene-D (7.62%). Density of essential oil from H. racemosum was 0.8978 (g/cm3) and the refractive index was 1.4911. Essential oil not showed biological activity against bacteria and fungi at the highest concentration evaluated (1000ug/mL). Further, the essential oil did not show antioxidant activity at any concentrations tested.